Nonlinear Reaction-Diffusion and Mediated Electron Transfer Process at Conducting Polymer Modified Ultramicroelectrodes (European Journal of Pure and Applied Mathematics, 2024)
The primary goal of this article is to present novel analytical solutions for the coupled nonlinear equation found in the mediated electron transfer process at polymer-modified conducting ultramicroelectrodes. Taylor’s series method is utilized to obtain approximate analytical solutions for the reaction-diffusion equations, allowing for the determination of the substrate and mediator concentrations and the current response concerning the substrate concentration at the electrode’s surface. The impact of different factors on concentration and current is also explored. The derived analytical results are in strong agreement with numerical results and with other analytical outcomes from the literature.
Keywords: Non-linear reaction-diffusion; Mathematical modeling; Taylor’s series; Michaelis–Menten kinetics